Land Degradation Analysis by Using Landscape Balance in Lebak Swamp Jakabaring South Sumatra - M. Edi Armanto; Elisa Wildayana (Journal of Wetlands Environmental Management, 2016)
This research aimed to analyze land degradation by using landscape balances in lebak swamp Jakabaring South Sumatra. The study was carried out in Jakabaring, South of Palembang. Field survey method was applied, the field observations and respondents were taken by randomly purposive sampling.Â  The interviews with farmers were done by using open questionnaire. The study resulted that erosion and abrasion rises above 1,000 % which includes the acreage of 1.16 % in 1988 to 12.34 % in 2015. The landscape becomes more dynamic from year to year (namely 88.75 % of normal landscape in 1988 and becoming 68.14 % in 2015). The drought in the lebak swamp is increasingly unpredictable, making it difficult for farmers to manage their farming activities. Deposited landscape was found about 272.43 ha (10.09 %) in 1988 and increased to approximately 527.04 ha (19.52 %) in 2015. Lebak swamp serves a lot of coming water from the upstream catchment area of approximately 3 million ha. This service is more and more complicated, irregular and burden lebak swamps.Â  The lebak swamp ecosystem has not only enormous potential, but also has a very high resilience.